The Influence of Price, Customer Satisfaction, And Service Quality on Community Welfare Is Mediated by an Increase in Community Income (Case Study of Clean Water Drilled Wells in Jirekan Hamlet, Sukodadi – Lamongan District) Partial Least Square Method An - Salmah Rosyida; Muhamad Imam Syairozi; Abid Muhtarom (Sean Institute, 2025)
The purpose of this study is to test and analyze the influence of price, customer satisfaction, and service quality on the increase in community income, as well as to test and analyze the influence of increasing community income on community welfare case study of clean water drilled wells in Jirekan Hamlet, Sukodadi – Lamongan District. In this study, 115 samples were used from the population of borehole clean water customers in Jirekan Hamlet, Balungtawun Village, Sukodadi District, Lamongan Regency. The method of collecting data is by means of interviews and distributing questionnaires to customers who buy clean water. Data analysis using the outer model consisted of validity tests and reliability tests, the inner models consisted of R-square, Path Coeficien, T-Statistic, Predictive Relavance, Model Fit, and as well as mediation tests and hypothesis tests. The results of the study show that prices have a positive but not significant effect on the variables of community welfare. Price variables have a positive and significant influence on the variable of increasing people's income. Customer satisfaction variables have a negative and significant influence on community welfare variables. The customer satisfaction variable has a negative and insignificant effect on the increase in people's income. The variable of service quality has a positive and significant influence on the variable of community welfare. The variable of service quality has a positive and significant influence on the variable of increasing public income. And the increase in community income has a positive and significant influence on the variables of community welfare